An original method of staining stroma - Cuadra C., Manuel (1956)
Described an original stromal staining method; it allows them neatly in blood smears off RBCs. Were also stained with the same method the "solenoids bodies" ("Halbmondkörper" in German, "bodies crescent" in Castilian, "crescent bodies" in English and "corps in demilune" in French), which, as we will to demonstrate in a forthcoming are a variety of stroma and its meaning has been clarified through the method. A small modification in the method yields very good colorations of organisms such as Bartonella baciliformis, Treponema pallidum, and Trichomonas Laverán Hematozoon vaginalis. It should be tested in other microorganisms.